HIV and Hepatitis B seroprevalence among the nepalese blood donors (Journal of Pathology of Nepal, 2013)
Background: HIV and Hepatitis B infections are public health problems in Nepal. This study was conducted based at NRCS/CBTS, with the objective of determining the HIV and HBsAg sero-prevalence in non-remunerated volunteer blood donors. Materials and Methods: A total of 66,904 units of blood collected, following donor recruitment criteriaduring March 2009-Sept. 2010 was included for analysis. All donated blood samples were subjected to screening for Transfusion transmitted infections including HIV and Hepatitis B surface antigen using standard ELISA test kits (Dade Behring, Germany). Initial reactive sera were re-tested for reconfi rmation with same test kits plus another test kit (Detect-HIV, Adaltis Inc, and Qualisa). Results: Out of 66,904 units of blood collected, 56,973 units were from male and 9,931 were from female donors. Among the total screened samples, 73 (0.10%) were found to be positive for HIV, {0.11% (64/56973) in male and 0.09% (9/9931) in female}; the difference between male and female donors (?2